Consumo de vancomicina 500 mg en los servicios de hospitalizacion del hospital nacional almanzor aguinaga asenjo - chiclayo - 2009 - Avalos Capristán, César Luis (2010)
This report corresponds to a descriptive study – retrospective cross section, whose purpose was designed to determine the consumption of vancomycin 500 mg in hospitalization services from Hospital National Almanzor Aguinaga Asenjo in 2009, To analyze consumer trends and to identify possible deviations in the use of this antibacterial. The data were obtained from the computer department of the hospital. The study population consisted of the registration data of patients hospitalized in the cardiology, thoracic surgery, intensive care unit, intermediate care unit and internal medicine in 2009. The annual consumption of vancomycin 500 mg for such services in 2009 was 7.92 DDD/100 beds / day. Intensive Care Unit (ICU) was presented a higher consumption of vancomycin 500 mg with 21.49 DDD/100 beds / day, followed by internal medicine services 7.12 DDD/100 beds / day, the cardiology service 5.48 DDD/100 beds / day, the thoracic surgery service with 3.98 DDD/100 / beds / day and finally the service intermediate care unit (INCU) with 1.52 DDD/100 beds / day. The trend of consumption in the cardiology, thoracic surgery and ICU showed no correlation between variables and no statistical significance, but in the INCU services and internal medicine shows trends to decrease and increase the consumption of vancomycin over of the months, respectively. The cost of treatment in the consumption of vancomycin 500 mg in the cardiology, thoracic surgery, ICU, INCU and Internal Medicine form HNAAA in 2009 was S /. 40941.04